2000
DOI: 10.1177/00912700022008612
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Coadministration May Increase Digoxin Concentrations by Inhibition of Intestinal P-Glycoprotein-Mediated Secretion

Abstract: The effect of atovarstatin on digoxin pharmacokinetics was assessed in 24 healthy volunteers in two studies. Subjects received 0.25 mg digoxin daily for 20 days, administered alone for the first 10 days and concomitantly with 10 mg or 80 mg atorvastatin for the last 10 days. Mean steady-state plasma digoxin concentrations were unchanged by administration of 10 mg atorvastatin. Mean steady-state plasma digoxin concentrations following administration of digoxin with 80 mg atorvastatin were slightly higher than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 10 publications
2
103
1
Order By: Relevance
“…The P-gp substrate activity of atorvastatin was also suggested by some other studies (Williams and Feely, 2002;Wu et al, 2000). Boyd et al found that 100 µM atorvastatin inhibited digoxin secretion in Caco-2 cells (transport from the basolateral to apical aspect of the monolayer) by 58%, equivalent to the inhibition observed with verapamil (Boyd et al, 2000). Another study showed that atorvastatin increased the bioavailability of digoxin (Lennernäs, 2003), which may be explained by the inhibition of P-gp by atorvastatin.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The P-gp substrate activity of atorvastatin was also suggested by some other studies (Williams and Feely, 2002;Wu et al, 2000). Boyd et al found that 100 µM atorvastatin inhibited digoxin secretion in Caco-2 cells (transport from the basolateral to apical aspect of the monolayer) by 58%, equivalent to the inhibition observed with verapamil (Boyd et al, 2000). Another study showed that atorvastatin increased the bioavailability of digoxin (Lennernäs, 2003), which may be explained by the inhibition of P-gp by atorvastatin.…”
Section: Discussionmentioning
confidence: 90%
“…Vatsa et al reported that atorvastatin is a moderate substrate for CYP P450 and is extensively metabolized via CYP P450-mediated oxidation and phase II glucuronidation both in humans and rats (Vatsa et al, 2012). The drug is a CYP3A4 substrate, and most of CYP3A4 substrates are P-gp substrates as well (Boyd et al, 2000). Vatsa et al stated that atorvastatin is a P-gp substrate at lower dose and an inhibitor at higher doses (Vatsa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that verapamil has a role on inhibition of P-glycoprotein (Pgp) which is a drug efflux pump. Inhibition of Pgp results in increased plasma level and subsequent longer duration of action of other drugs used with verapamil [14] . HR in SAL showed significant increases after induction of anaesthesia, which is remained high in the whole assessment period compared with the base.…”
Section: Discussionmentioning
confidence: 99%
“…We had 4 pDDIs of digoxin used together with atorvastatin which could lead to an increase in plasma concentration of digoxin (up to 20%) and consequently digoxin's adverse reactions [27], 4 pDDIs of acenocoumarol and rosuvastatin which may result in increase of international normalized ratio (INR) and increased risk of bleeding [28] and 3 pDDIs of carbamazepine and atorvastatin (2 cases) and lovastatin (1 case) that could result in decreased exposure to the statin and consequently a lower efficacy. None of these pDDIs had clinical outcome.…”
Section: Discussionmentioning
confidence: 99%